Macrophage nuclear factor erythroid 2‐related factor 2 deficiency promotes innate immune activation by tissue inhibitor of metalloproteinase 3–mediated RhoA/ROCK pathway in the ischemic liver. Issue 6 (10th December 2021) - Rao, Jianhua; Qiu, Jiannan; Ni, Ming; Wang, Hao; Wang, Peng; Zhang, Lei; Wang, Zeng; Liu, Mu; Cheng, Feng; Wang, Xuehao; Lu, Ling
Abstract: Background and Aims: Nuclear factor erythroid 2‐related factor 2 (Nrf2) is a master regulator of reactive oxygen species (ROS) and inflammation and has been implicated in both human and murine inflammatory disease models. We aimed to characterize the roles of macrophage‐specific Nrf2 in liver ischemia/reperfusion injury (IRI). Approach and Results: First, macrophage Nrf2 expression and liver injury in patients undergoing OLT or ischemia‐related hepatectomy were analyzed. Subsequently, we created a myeloid‐specific Nrf2‐knockout (Nrf2 M‐KO ) strain to study the function and mechanism of macrophage Nrf2 in a murine liver IRI model. In human specimens, macrophage Nrf2 expression was significantly increased in liver tissues after transplantation or hepatectomy. Interestingly, lower Nrf2 expressions correlated with more severe liver injury postoperatively. In a mouse model, we found Nrf2 M‐KO mice showed worse hepatocellular damage than Nrf2‐proficient controls based on serum biochemistry, pathology, ROS, and inflammation. In vitro, Nrf2 deficiency promoted innate immune activation and migration in macrophages on toll‐like receptor (TLR) 4 stimulation. Microarray profiling showed Nrf2 deletion caused markedly lower transcriptional levels of tissue inhibitor of metalloproteinase 3 (Timp3). ChIP‐seq, PCR, and luciferase reporter assay further demonstrated Nrf2 bound to the promoter region of Timp3. Moreover, a disintegrin and metalloproteinase (ADAM) 10/ROCK1 was specifically increased in Nrf2‐deficient macrophages. Increasing Timp3 expression effectively inhibited ADAM10/ROCK1 expression and rescued the Nrf2 M‐KO ‐mediated inflammatory response on TLR4 stimulation in vitro. Importantly, Timp3 overexpression, recombinant Timp3 protein, or ROCK1 knockdown rescued Nrf2 M‐KO ‐related liver IRI by inhibiting macrophage activation. Conclusions: In conclusion, macrophage Nrf2 mediates innate proinflammatory responses, attenuates liver IRI by binding to Timp3, and inhibits the RhoA/ROCK pathway, which provides a therapeutic target for clinical organ IRI.